2022
DOI: 10.3390/brainsci12020273
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity Signatures Underlying Simultaneous Language Translation in Interpreters and Non-Interpreters of Mandarin and English: An fNIRS Study

Abstract: Recent neuroimaging research has suggested that interpreters and non-interpreters elicit different brain activation patterns during simultaneous language translation. However, whether these two groups have different functional connectivity during such a task, and how the neural coupling is among brain subregions, are still not well understood. In this study, we recruited Mandarin (L1)/English (L2) interpreters and non-interpreter bilinguals, whom we asked to perform simultaneous language translation and readin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Broca’s area (left inferior frontal gyrus (lIFG)/BA 44/45) has been implicated in various language-related tasks via a variety of neuroimaging techniques. To name a few, fMRI has indicated that the lIFG plays a role in phonetic encoding (Papoutsi et al, 2009); MEG/fMRI has shown stronger activation of Broca’s area during verb generation (Pang, Wang, Malone, Kadis, & Donner, 2011); electrocorticography has revealed a cortical network for speech planning that includes Broca’s area (Castellucci, Kovach, Howard, Greenlee, & Long, 2022), and fNIRS has shown that bilingual interpretation relies on functional connectivity between Broca’s area and Wernicke’s area (He & Hu, 2022). While these studies offer strong correlational evidence, they are, by nature, correlation studies.…”
Section: Introductionmentioning
confidence: 99%
“…Broca’s area (left inferior frontal gyrus (lIFG)/BA 44/45) has been implicated in various language-related tasks via a variety of neuroimaging techniques. To name a few, fMRI has indicated that the lIFG plays a role in phonetic encoding (Papoutsi et al, 2009); MEG/fMRI has shown stronger activation of Broca’s area during verb generation (Pang, Wang, Malone, Kadis, & Donner, 2011); electrocorticography has revealed a cortical network for speech planning that includes Broca’s area (Castellucci, Kovach, Howard, Greenlee, & Long, 2022), and fNIRS has shown that bilingual interpretation relies on functional connectivity between Broca’s area and Wernicke’s area (He & Hu, 2022). While these studies offer strong correlational evidence, they are, by nature, correlation studies.…”
Section: Introductionmentioning
confidence: 99%